2022
DOI: 10.5334/jbsr.2741
|View full text |Cite
|
Sign up to set email alerts
|

Elective Transjugular Intrahepatic Portosystemic Shunt Using Viatorr Stent-Grafts: A Single-Center Experience from China

Abstract: Background and Aims: Transjugular intrahepatic portosystemic shunt (TIPS) is a well-established approach for the management of variceal bleeding, refractory ascites, hepatic hydrothorax, and preoperative treatment of portal hypertension prior to major abdominal surgery in patients with compensated cirrhosis, and so on. This study aimed to investigate the safety and long-term efficacy of TIPS implantation using Viatorr TIPS stent-grafts. Material and Methods: A cohort of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…Zhou et al found a cumulative survival rate of 91.9% at 1 year following stent-graft insertion (20). LI et al reported the cumulative mortality at 2 years was 12.3% (19). Our results are consistent with these studies, which validates the e cacy of TIPS with Viatorr stents in reducing mortality for these patients.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Zhou et al found a cumulative survival rate of 91.9% at 1 year following stent-graft insertion (20). LI et al reported the cumulative mortality at 2 years was 12.3% (19). Our results are consistent with these studies, which validates the e cacy of TIPS with Viatorr stents in reducing mortality for these patients.…”
Section: Discussionsupporting
confidence: 92%
“…Shunt dysfunctions continue to be a signi cant concern regarding TIPS insertion over the long term. Four studies from Chinese and western countries using Viatorr stents have found 2-year risks of 6.9-23.7%, which was similar to our study (19)(20)(21)(22). Zhou et al reported the highest 2-year risk of 23.7%.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The 1-, 4- and 10-year survival rates were 69.2%, 52.1% and 30.7%, respectively. In a retrospective single-center study by Li et al [ 28 ] including 59 cirrhotic patients with CSPH, elective TIPS implantation using VTS stent grafts contributed to a decrease in PSPG from 21 mmHg (interquartile range: 19-25) to 13 mmHg (interquartile range: 10-16). The cumulative rate of overall mortality was 34.2% at five years.…”
Section: Evolution Of Technical Refinements Of Tips Stentsmentioning
confidence: 99%